Actividad in vitro de doripenem comparado con meropenem frente a aislamientos de Pseudomonas aeruginosa en un centro asistencial de tercer nivel de Bogotá (Colombia) Activity of Doripenem compared to Meropenem against Pseudomonas aeruginosa isolates at Tertiary Care Teaching Hospital in Bogotá (Colombia) - Adriana Jiménez (Infectio, 2012)
Objetivo: El objetivo de este estudio fue evaluar la actividad in vitro de doripenem comparado con meropenem frente a aislamientos locales de Pseudomonas aeruginosa (P. aeruginosa) . Materiales y métodos: En el Hospital San José de Bogotá (Colombia), un hospital universitario de 300 camas, se recolectaron entre 2009 y 2011, 83 aislamientos no repetidos de P. aeruginosa , en los cuales se determinó la concentración inhibitoria mínima frente a meropenem y doripenem por el método de E-test. Se aplicaron los puntos de corte del Clinical and Laboratory Standars Institute para carbapenémicos vigentes para 2012 Resultados: La sensibilidad global de los aislamientos de P. aeruginosa a meropenem fue del 69% y a doripenem del 75%, siendo la concentración inhibitoria mínima 50 y 90 (µg/mL) de 0,75 y 28,8 para meropenem y de 0,64 y 15,2 para doripenem. Conclusiones: La concentración inhibitoria mínima frente a doripenem fue menor que la correspondiente a meropenem. Se requiere realizar en el ámbito local estudios de este tipo con el fin de llevar a cabo los ajustes a los protocolos de antibióticos institucionales. objective: The aim of this study was to evaluate the in vitro activity of doripenem compared to meropemen against local isolates of Pseudomonas aeruginosa (P. aeruginosa) . Materials and methods: At the San José Hospital in Bogotá-Colombia, a 300-bed teaching hospital, 83 nonduplicate isolates of P. aeruginosa were collected between 2009 and 2011.Meropenem and Doripenem Minimum Inhibitory Concentration (MIC) were determined by the E test method. The 2012 Clinical and Laboratory Standards Institute breakpoints for carbapenems were applied. Results: The global susceptibility of P. aeruginosa isolates to meropemen was 69% and to doripenem was 75%, being the CIM 50 and 90 (ug/mL) of 0.75 and 28.8 for meropenem and of 0.64 and 15.2 for doripenem. Conclusions: The MIC of doripenem was lower than the corresponding MIC of meropenem. It is required to carry out local studies of this type in order to make adjustments to the institutional antibiotics protocol.